Anatomical Society core regional anatomy syllabus for undergraduate medicine: the Delphi process. Issue 1 (27th November 2015) - Smith, C.F.; Finn, G. M.; Stewart, J.; McHanwell, S.
Abstract: A modified Delphi method was employed to seek consensus when revising the UK and Ireland's core syllabus for regional anatomy in undergraduate medicine. A Delphi panel was constructed involving 'expert' (individuals with at least 5 years' experience in teaching medical students anatomy at the level required for graduation). The panel ( n = 39) was selected and nominated by members of Council and/or the Education Committee of the Anatomical Society and included a range of specialists including surgeons, radiologists and anatomists. The experts were asked in two stages to 'accept', 'reject' or 'modify' (first stage only) each learning outcome. A third stage, which was not part of the Delphi method, then allowed the original authors of the syllabus to make changes either to correct any anatomical errors or to make minor syntax changes. From the original syllabus of 182 learning outcomes, removing the neuroanatomy component (163), 23 learning outcomes (15%) remained unchanged, seven learning outcomes were removed and two new learning outcomes added. The remaining 133 learning outcomes were modified. All learning outcomes on the new core syllabus achieved over 90% acceptance by the panel.